Effects of Organic and Inorganic Fertilizers on Cucumber (Cucumis sativus) Production - Mumo, Catherine Kuthea (University of Embu, 2019)
Cucumber (Cucumis sativus) is a crop which is becoming an economically important vegetable in Kenya despite its low nutrient application levels. A field research was carried out at the University of Embu demonstration farm with the aim of determining the effect of organic and inorganic fertilizers on cucumber production. The trial was laid in a Randomized Complete Block Design with three treatments; T1- organic manure (poultry manure) at a rate of 10-15 tonnes per hectare, T2-inorganic fertilizer (CAN) at a rate of 200 kg per hectare and T3- control replicated three times. The parameters assessed were plant height, number of leaves, stem diameter, number of flowers and the leaf index area. The data was subjected to ANOVA using the R-software and mean comparison were done by LSD. The study showed that T1 had the highest leaf size and plant height but took more days to flower while T2 had medium leaf size, plant height and took few days to flower. It is recommended that the study be repeated for another season since the results of this study are based on one season.